2014
DOI: 10.1111/pan.12588
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pediatric perioperative risk assessment by ASA physical status and by NARCOSS (neurological, airway, respiratory, cardiovascular, other–surgical severity) scores

Abstract: NARCO-SS is a valid risk stratification tool that is better than the ASA-PS in discriminating children with adverse perioperative outcomes. The poor calibration of both scores suggests neither can reliably predict perioperative outcomes in individual patients. Modification of neurological and airway categories may improve the predictive accuracy of the NARCO-SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 18 publications
0
38
0
7
Order By: Relevance
“…Although this finding may seem intuitive, it is important to convey because the preoperative active health issues in the current study are not routinely included in existing tools that are used to assess surgical risk. [12][13][14][15][16][17][18][19][20] Rather, those tools emphasize the presence of a chronic condition in a specific organ system (eg, respiratory) without incorporating perioperative clinical judgment on the effects of that condition and its impact on the child's perioperative health and safety. In the CART analysis of the current study, it was revealed that preoperative active health issues had the strongest influence on PoPD with lower-risk procedures (eg, tonsillectomy or adenoidectomy); for those procedures, PoPD was nearly 80% more likely in patients with versus without a preoperative active health issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this finding may seem intuitive, it is important to convey because the preoperative active health issues in the current study are not routinely included in existing tools that are used to assess surgical risk. [12][13][14][15][16][17][18][19][20] Rather, those tools emphasize the presence of a chronic condition in a specific organ system (eg, respiratory) without incorporating perioperative clinical judgment on the effects of that condition and its impact on the child's perioperative health and safety. In the CART analysis of the current study, it was revealed that preoperative active health issues had the strongest influence on PoPD with lower-risk procedures (eg, tonsillectomy or adenoidectomy); for those procedures, PoPD was nearly 80% more likely in patients with versus without a preoperative active health issue.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Existing tools with a predominate focus on chronic conditions (eg, oncologic diseases and neuromuscular disorders) that are used to predict specific pediatric surgical complications have been helpful in this area. [12][13][14][15][16][17][18][19][20] However, previous studies and our clinical experience suggest that clinicians continue to subjectively assess and imprecisely convey surgical risks. 21 There are 2 key gaps in knowledge that, when filled, may help this situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Do sada jedinu nezavisnu ocjenu značajka mjernog sustava NARCO-SS i usporedbu njegove pouzdanosti u procjeni perioperacijskih ishoda s ASA-inim statusom proveli su Udupa A. i suradnici. 25 Oni zaključuju da je NARCO-SS vrijedan alat za procjenu rizika koji bolje korelira sa stopom neželjenih ishoda anestezije u djece u odnosu prema prediktivnoj vrijednosti ASA-ina statusa. Sustav NARCO-SS kritiziran je zbog svoje složenosti te se postavilo pitanje je li praktičan.…”
Section: Bodovni Sustav Narco-ss Procjene Prijeanestezijskog Rizika Uunclassified
“…Esse sistema mostra taxa preditiva mais acurada de eventos adversos e possibilita mais intensificação de cuidados, comparado ao ASA-os. 4 ro especial, favorecendo o planejamento perioperatório, baseado no uso apropriado dos recursos hospitalares e programação das atividades cirúrgicas de acordo com as características clínicas do paciente. 2…”
unclassified